Fat Grafting for Recontouring Sunken Upper Eyelids With Multiple Folds in Asians—Novel Mechanism for Neoformation of Double Eyelid Crease. Issue 4 (April 2016) - Lin, Tsai-Ming; Lin, Tsung-Ying; Huang, Yu-Hao; Hsieh, Tung-Ying; Chou, Chih-Kang; Takahashi, Hidenobu; Lai, Chung-Sheng; Lin, Sin-Daw
Abstract : Background: This study reviewed the mini invasive technique, microautologous fat transplantation (MAFT), as a strategy in simultaneously treating sunken upper eyelids with multiple folds and recreating a double eyelid crease in Asian people. Methods: The MAFT was performed with the assistance of a patented medical device, the MAFT-GUN, on 34 patients who had sunken upper eyelids and multiple folds. Each delivered fat parcel was accurately and consistently maintained at 1/240 mL during placement. Follow-up was regularly performed with photography for comparison. Results: Fifty-eight sunken upper eyelids with multiple folds were reconstructed. In addition to the ameliorative recontouring of hollowness, a natural eyelid crease was created postoperatively. Temporary swelling and bruising were noted several days after surgery without morbidities, such as fibrosis or nodulation. All of the patients were satisfied with the 1-time MAFT procedure. Conclusions: Fat grafting for sunken upper eyelids with multiple folds has been reported in the literature. However, temporal effects and complications, such as nodulation and irregularity, have often occurred. A new method, MAFT, demonstrated its reliability as a modality for sunken upper eyelids with multiple folds in Asians. Moreover, MAFT might serve as an alternative for neoformation of double eyelids in these candidates. Abstract : Supplemental digital content is available in the text.